1996
DOI: 10.1177/002246699603000204
|View full text |Cite
|
Sign up to set email alerts
|

Supports and Resources Associated with Inclusive Schooling: Perceptions of Elementary School Teachers about Need and Availability

Abstract: A mail survey of elementary education teachers was conducted to identify their perceptions of the necessity and availability of various resources and supports for including students with disabilities in their classrooms. Of the 2,100 questionnaires mailed to kindergarten through Grade 6 teachers, 1,430 (68.1%) were returned in usable form with at least 64% from each grade level and at least 65% returned from each geographic region of the United States. Based on the respondents' ratings, they were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…Werts et al (1996b) compared the availability of and need for varying supports and resources as reported by teachers in inclusive school settings. Their study revealed that the teachers of pupils with overall higher impairment ratings expressed greater discrepancies between the present and ideal situation in regard to training, material resources, additional personal support and time for contact with others and participating in meetings.…”
Section: Child Characteristics In Uencing the Classroom Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Werts et al (1996b) compared the availability of and need for varying supports and resources as reported by teachers in inclusive school settings. Their study revealed that the teachers of pupils with overall higher impairment ratings expressed greater discrepancies between the present and ideal situation in regard to training, material resources, additional personal support and time for contact with others and participating in meetings.…”
Section: Child Characteristics In Uencing the Classroom Systemmentioning
confidence: 99%
“…Research has examined the perceived needs of parents (Bailey and Simeonsson, 1988;Bailey et al, 1992;Granlund et al, 1994), family adaptations (Gallimore et al, 1996); teachers' perceptions of their needs (Werts et al, 1996a(Werts et al, , 1996bRollPettersson, 2001), and teacher self-ef cacy (Soodak and Podell, 1993). Relatively little research, however, has compared the perceived needs of different environments containing the same child.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern is that including large numbers of children with disabilities will make it too difficult for teachers to meet the needs of individual students because of the demands on their time. Although in theory increases in resources would mitigate these effects, typical school districts do not greatly increase the resources provided when restructuring for inclusion (Werts, Wolery, Snyder, Caldwell, & Salisbury, 1996).…”
mentioning
confidence: 97%
“…Finally, research literature also supports the idea that a teachers' acceptance of instructional adaptations is related to the level of support he or she receives from the administration and the school (Scott, Vitale, & Masten, 1998). Werts, Woley, Zinder, Caldwell, and Salisbury (1996) highlighted the existence of a positive relationship between the quantity and quality of support and resources, and the use of instructional adaptations. Teachers keep requesting more time, personal support, and material resources to address students' special educational needs (Hughes & Martínez Valle-Riestra, 2007;Schumm et al, 1995).…”
Section: Introductionmentioning
confidence: 89%